A Virtual Class Tool for Facial Expressions Telemonitoring through Embedded Systems - Preto, Murilo de Souza; Ferreira, Fernando Teubl; Kurashima, Celso Setsuo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
In recent years, there has been a transition from face-to-face class meetings to videoconferences, which has been further expanded during the COVID-19 pandemic. In the area of education, remote classes entailed new advantages and some challenges – in one hand, allowing for an extended time and location flexibility – while, in the other hand, operating in a inexpressive, distanced, manner. Aiming to increase non-verbal communication in virtual class meetings, this research explores the technical feasibility and potential implementation challenges of developing a virtual class tool for facial expressions telemonitoring through embedded systems. As a suggested solution, a system which allows for a teacher to remotely follow the facial expressions of students through real-time rendered graphical data was developed. Technical experimental results include: an average recognition accuracy of 57%, for all facial expressions, peaking at 80% for happiness, in a median processing time of 2.85 seconds with a Raspberry Pi 4B, and of 0.572 seconds with a commodity computer. These findings highlight the technical viability of the implemented system, possibly allowing to decrease the lack of non-verbal communication in distanced learning.